2017
DOI: 10.1073/pnas.1703728114
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine induces gastric acid secretion via bitter taste signaling in gastric parietal cells

Abstract: Caffeine, generally known as a stimulant of gastric acid secretion (GAS), is a bitter-tasting compound that activates several taste type 2 bitter receptors (TAS2Rs). TAS2Rs are expressed in the mouth and in several extraoral sites, e.g., in the gastrointestinal tract, in which their functional role still needs to be clarified. We hypothesized that caffeine evokes effects on GAS by activation of oral and gastric TAS2Rs and demonstrate that caffeine, when administered encapsulated, stimulates GAS, whereas oral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
186
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(203 citation statements)
references
References 42 publications
8
186
1
4
Order By: Relevance
“…Compounds reported previously to activate TAS2Rs are indicated by #, compounds for which the activation of TAS2Rs could not be confirmed are labeled by §. Examples for TAS2Rs that have been associated with non‐gustatory functions in brain, gastrointestinal tissues, respiratory epithelia, thyroid gland, leukocytes, and vascular smooth muscle cells are printed in bold.…”
Section: Resultsmentioning
confidence: 99%
“…Compounds reported previously to activate TAS2Rs are indicated by #, compounds for which the activation of TAS2Rs could not be confirmed are labeled by §. Examples for TAS2Rs that have been associated with non‐gustatory functions in brain, gastrointestinal tissues, respiratory epithelia, thyroid gland, leukocytes, and vascular smooth muscle cells are printed in bold.…”
Section: Resultsmentioning
confidence: 99%
“…The colocalization of TAS2R10 with the ghrelin cell and the strong stimulatory effect of the TAS2R10 agonist, erythromycin A, on ghrelin secretion point toward an important role of TAS2R10. Previous studies have shown that TAS2R10 was also expressed in human gastric parietal cells (55).…”
Section: Discussionmentioning
confidence: 96%
“…In view of possible implications it will be of great interest to further explore whether individual combinations of receptor types may be expressed in distinct cell types or in cells at certain positions. This would allow defined responses to various bitter compounds and may explain diverse effects of bitter compounds on stomach functions, such as gastric emptying (Glendinning et al, 2008), antral contractility, stimulation of ghrelin release (Janssen et al, 2011(Janssen et al, , 2012Wang et al, 2019) and induction of gastric acid secretion (Liszt et al, 2017(Liszt et al, , 2018.…”
Section: Discussionmentioning
confidence: 99%
“…However, very little is known about the expression of bitter receptors in the stomach. The current information is mainly based on PCR analyses (Wu et al, 2002(Wu et al, , 2005Vegezzi et al, 2014;Prandi et al, 2018); only recently immunohistochemical evidence was presented for the presence of TAS2R10 receptor protein in parietal and chief cells of human stomach (Liszt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%